PENGARUH LINGKUNGAN SOSIAL DAN POLA ASUH ORANG TUA TERHADAP MORAL REMAJA BUDDHIS DI KECAMATAN PONGGOK KABUPATEN BLITAR - Hana Prastila Raxsa; Tri Yatno; Niken Wardani (STABN RADEN WIJAYA WONOGIRI, 2020)
Moral decline in teenagers can be seen from the number of delinquency cases committed byjuveniles. The cause of the decline of moral teens can be influenced by the environmental community andparenting parents. Community environmental impacts on teenagers because teenagers do every dayinteraction with the surrounding environment. While parents are a major factor in giving moral education inthe family environment. Based on the observation of social and environmental researchers parenting parentshave an influence on the moral formation of adolescents. It is what lies behind the researcher to conductresearch in order to determine how much influence the social environment and upbringing of parents toadolescent moral Buddhist. This study used quantitative research methods to a survey conducted in theDistrict Ponggok Blitar June-September 2016. Subjects in this study were young Buddhist in DistrictPonggok. Instruments and techniques of data collection is done by using a questionnaire. Data wereanalyzed using SPSS versoin 15. Based on the research and analysis of the data showed that the influence ofsocial environment on adolescent moral Buddhists in Sub Ponggok amounted to 0,293. The influence ofparenting parents on adolescent moral Buddhist in Sub Ponggok at 0,170. While the influence of the socialenvironment and upbringing of parents to adolescent moral Buddhists in Sub Ponggok of 0,626.